Safety and immunogenicity of mRNA-LNP COVID-19 vaccine CVnCoV in Latin American adults: A phase 2 randomized study. (August 2022) - Sáez-Llorens, Xavier; Lanata, Claudio; Aranguren, Elaine; Celis, Carlos R.; Cornejo, Rubelio; DeAntonio, Rodrigo; Ecker, Lucie; Garrido, Diegi; Gil, Ana I.; Gonzales, Marina; Hess-Holtz, Morgan; Leroux-Roels, Geert; et al.
Highlights: Two 12 µg CVnCoV doses are immunogenic against S-protein in adults. Immune responses were lower in > 60 year-olds than 18–60 year-olds. Distinct neutralizing antibody and CD4 + T cell responses to S-protein were induced. Booster doses increased responses to S-protein showing immune memory was induced. Three 12 µg doses are well tolerated with mainly mild to moderate adverse events. Abstract: Background: The COVID-19 vaccine candidate CVnCoV comprises sequence-optimized mRNA encoding SARS-CoV-2 S-protein encapsulated in lipid nanoparticles. In this phase 2a study, we assessed reactogenicity and immunogenicity of two or three doses in younger and older adults. Methods: Younger (18–60 years) and older (>60 years) adults were enrolled in two sites in Panama and Peru to receive either 6 or 12 µg doses of CVnCoV or licensed control vaccines 28 days apart; subsets received a 12 µg booster dose on Day 57 or Day 180. Solicited adverse events (AE) were reported for 7 days and unsolicited AEs for 4 weeks after each vaccination, and serious AEs (SAE) throughout the study. Humoral immunogenicity was measured as neutralizing and receptor binding domain (RBD) IgG antibodies and cellular immunogenicity was assessed as CD4+/CD8 + T cell responses. Results: A total of 668 participants were vaccinated (332 aged 18–60 years and 336 aged > 60 years) including 75 who received homologous booster doses. Vaccination was well tolerated with no vaccine-related SAEs. Solicited and unsolicited AEs were mainly mild to moderate and resolved spontaneously. Both age groups demonstrated robust immune responses as neutralizing antibodies or RBD-binding IgG, after two doses, with lower titers in the older age group than the younger adults. Neither group achieved levels observed in human convalescent sera (HCS), but did equal or surpass HCS levels following homologous booster doses. Following CVnCoV vaccination, robust SARS-CoV-2 S-protein-specific CD4 + T-cell responses were observed in both age groups with CD8 + T-cell responses in some individuals, consistent with observations in convalescing COVID-19 patients after natural infection. Conclusions: We confirmed that two 12 µg doses of CVnCoV had an acceptable safety profile, and induced robust immune responses. Marked humoral immune responses to homologous boosters suggest two doses had induced immune memory.